2017
DOI: 10.1089/scd.2017.0090
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Human Induced Pluripotent Stem Cell Expansion in Stirred-Suspension Culture

Abstract: Human induced pluripotent stem cells (hiPSCs) hold great hopes for application in regenerative medicine due to their inherent capacity to self-renew and differentiate into cells from the three embryonic germ layers. For clinical applications, a large quantity of hiPSCs produced in standardized and scalable culture processes is required. Several groups, including ours, have developed methodologies for scaled-up hiPSC production in stirred bioreactors in chemically defined medium. In this study, we optimized the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Our future studies will focus on translating these protocols to hESC and hiPSC lines. Although human pluripotent cells are more challenging to work with, numerous authors have shown expansion and chromosomal normality following single‐cell inoculation (Abbasalizadeh, Larijani, Samadian, & Baharvand, 2012; Abecasis et al, 2017; Haraguchi, Matsuura, Shimizu, Yamato, & Okano, 2015; Kwok et al, 2018) and aggregate preformation (Hunt, Meng, Rancourt, Gates, & Kallos, 2014; Meng, Liu, Poon, & Rancourt, 2017) into stirred suspension bioreactors. As our lab has had success with translating bioprocess protocols from mouse to human stem cells in the past (Baghbaderani et al, 2008; Gilbertson, Sen, Behie, & Kallos, 2006) and are hopeful this can be replicated with our PSC work.…”
Section: Discussionmentioning
confidence: 99%
“…Our future studies will focus on translating these protocols to hESC and hiPSC lines. Although human pluripotent cells are more challenging to work with, numerous authors have shown expansion and chromosomal normality following single‐cell inoculation (Abbasalizadeh, Larijani, Samadian, & Baharvand, 2012; Abecasis et al, 2017; Haraguchi, Matsuura, Shimizu, Yamato, & Okano, 2015; Kwok et al, 2018) and aggregate preformation (Hunt, Meng, Rancourt, Gates, & Kallos, 2014; Meng, Liu, Poon, & Rancourt, 2017) into stirred suspension bioreactors. As our lab has had success with translating bioprocess protocols from mouse to human stem cells in the past (Baghbaderani et al, 2008; Gilbertson, Sen, Behie, & Kallos, 2006) and are hopeful this can be replicated with our PSC work.…”
Section: Discussionmentioning
confidence: 99%
“…The change in size distribution of aggregate is affected directly by cell division, or indirectly by joining of new cells from outside and the association of smaller aggregates to form larger ones, the breakage of aggregates to form smaller ones, cell growth, and death owing to the stress caused by fluid motion . The bioreactor's operating parameters determine the distribution of aggregates in a culture fluid, size of the aggregates, and expansion capacity through controlling amount of shear force applied on the cells . Agitation and shear stress, which are concurrently making and breaking cell–cell and cell–substrate interactions within cell aggregates, may have adverse effects on aggregate morphology and growth kinetics.…”
Section: Bioprocess Design Considerations To Enhance Scalable Expansimentioning
confidence: 99%
“…Once aggregates have formed, they gather at the bottom of the culture vessel due to the lack of mixing and generate larger aggregates owing to fusion of aggregates, leading to cell death at the central region of the aggregates. Many studies have been carried out to gain knowledge on shear stress fluid shear stress caused by mixing in the bioreactor as a function of cell types . Cormier et al reported that mouse ESCs (mESCs) successfully expanded as aggregates in spinner flasks at an agitation of 80–100 rpm which corresponds to a shear stress in the range from 4.5 to 6.1 dyn cm −2 .…”
Section: Bioprocess Design Considerations To Enhance Scalable Expansimentioning
confidence: 99%
See 2 more Smart Citations